Bi-directional communication at the neurovascular unit: implications for neuronal function - Filosa, Jessica A. (Henry Stewart Talks, 2016)
The anatomical organization of cerebral vessels and corresponding innervations, Neurovascular coupling mechanism: emphasis on K+ signaling, Novel in vitro model to study neurovascular coupling in the brain, Reverse flow of communication at the neurovascular unit: vascular-to-glia communication